The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1073/pnas.1015171108
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of tumor initiating cells of defined genetic composition by nucleostemin

Abstract: Recent work has identified a subset of cells resident in tumors that exhibit properties similar to those found in normal stem cells. Such cells are highly tumorigenic and may be involved in resistance to treatment. However, the genes that regulate the tumor initiating cell (TIC) state are unknown. Here, we show that overexpression of either of the nucleolar GTP-binding proteins nucleostemin (NS) or GNL3L drives the fraction of genetically defined tumor cells that exhibit markers and tumorigenic properties of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(137 citation statements)
references
References 45 publications
8
128
1
Order By: Relevance
“…In this vein, Bill Hahn explored the activity of an alternative complex formed by TERT, BRG1 (a chromatin remodeling ATPase implicated in the transcriptional regulation of many target genes), and NS/ GNL3L (two related proteins that are highly expressed in proliferative, multipotential cells). He found that overexpression of NS or GNL3L increased the fraction of TICs (tumor initiating cells or tumor stem cells) in a cell population (61). Consistent with working through a nontelomere-related pathway, the effect was not accompanied by telomere length alterations and was abolished by knockdown of BRG1 and TERT but not TERC (the TER gene).…”
Section: Regulation By Telomere Proteins and Accessory Factorsmentioning
confidence: 55%
“…In this vein, Bill Hahn explored the activity of an alternative complex formed by TERT, BRG1 (a chromatin remodeling ATPase implicated in the transcriptional regulation of many target genes), and NS/ GNL3L (two related proteins that are highly expressed in proliferative, multipotential cells). He found that overexpression of NS or GNL3L increased the fraction of TICs (tumor initiating cells or tumor stem cells) in a cell population (61). Consistent with working through a nontelomere-related pathway, the effect was not accompanied by telomere length alterations and was abolished by knockdown of BRG1 and TERT but not TERC (the TER gene).…”
Section: Regulation By Telomere Proteins and Accessory Factorsmentioning
confidence: 55%
“…As a result, chromatin regulators Bmi1 and HMGA2 demonstrated a tendency to be highly expressed in tumors. In addition, CD44, 15 GNL3L/ nucleostemin, 16 and YBX1 17 showed higher average expression in tumors. By contrast, EpCAM, CD133 (Prominin 1), 18 and SHH expression levels showed great variability among individual cases.…”
Section: Discussionmentioning
confidence: 99%
“…Okamoto and coworkers identified TERT as a necessary component to maintain a stem cell state of the tumour-initiating cells (TIC) (Okamoto et al 2011). The formation of a complex TERT-GNL3L/NS, which are proposed as markers for TICs in highly aggressive tumours, seems to contribute directly to cancer stem cell formation (Okamoto et al 2011).…”
Section: Role Of Tert In Proliferation Invasion and Tumourigenesismentioning
confidence: 99%
“…The formation of a complex TERT-GNL3L/NS, which are proposed as markers for TICs in highly aggressive tumours, seems to contribute directly to cancer stem cell formation (Okamoto et al 2011).…”
Section: Role Of Tert In Proliferation Invasion and Tumourigenesismentioning
confidence: 99%